The Concept Of Faith In Islamic Theology As A Foundation For Deradicalization In Islamic Education - Mutia Rahmawati; M. Noor Fuady; Asikinnor Asikinnor (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2026)
This study aims to analyze the concept of faith (īmān) in Islamic theology (‘ilm al-kalām) and to examine its potential as a foundational framework for deradicalization in Islamic education. The research employs a qualitative library research method, drawing on classical and contemporary theological works representing major schools of Islamic thought, as well as recent studies on radicalism in educational contexts. Data are analyzed using a descriptive-analytical approach to identify key theological principles that promote moderation, tolerance, and balanced religiosity. The findings reveal that the theological understanding of faith, particularly the integration of belief, verbal affirmation, and ethical action, provides a comprehensive basis for cultivating inclusive and non-extremist attitudes among learners. Moreover, the reinterpretation of faith within a contextual and educational framework contributes to strengthening critical thinking, religious moderation, and resilience against radical ideologies. This study concludes that the concept of faith in Islamic theology can serve as a strategic and transformative foundation for deradicalization efforts in Islamic education, especially in responding to contemporary challenges in Indonesia’s pluralistic society